2013
DOI: 10.1186/1742-2094-10-23
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4 mediates microglial activation and production of inflammatory mediators in neonatal rat brain following hypoxia: role of TLR4 in hypoxic microglia

Abstract: BackgroundHypoxia induces microglial activation which causes damage to the developing brain. Microglia derived inflammatory mediators may contribute to this process. Toll-like receptor 4 (TLR4) has been reported to induce microglial activation and cytokines production in brain injuries; however, its role in hypoxic injury remains uncertain. We investigate here TLR4 expression and its roles in neuroinflammation in neonatal rats following hypoxic injury.MethodsOne day old Wistar rats were subjected to hypoxia fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
181
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(194 citation statements)
references
References 50 publications
9
181
1
3
Order By: Relevance
“…LPS caused neuronal injury in co-cultures prepared from wild-type mice but did not induce neuronal injury in cocultures derived from TLR4 mutant mice (Lehnardt et al 2003). Increased TLR4 expression could be involved in excessive neuroinflammation during brain hypoxia/ischemia (Hughes 2012;De Paola et al 2012;Kilic et al 2008;Yao et al 2013). Therefore, TLR4 abnormal expression or excessive immune reaction would cause damage to the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…LPS caused neuronal injury in co-cultures prepared from wild-type mice but did not induce neuronal injury in cocultures derived from TLR4 mutant mice (Lehnardt et al 2003). Increased TLR4 expression could be involved in excessive neuroinflammation during brain hypoxia/ischemia (Hughes 2012;De Paola et al 2012;Kilic et al 2008;Yao et al 2013). Therefore, TLR4 abnormal expression or excessive immune reaction would cause damage to the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Among the identified TLRs, TLR4 is expressed on microglia and participates in activation of these cells induced by various stressful events in the brain. 33,34) Several studies have reported that TLR4-dependent activation of microglia is involved in depressive disorder. 35,36) TLR4 may be activated by the cytokines such as IL-1β secreted by microglia cells, then further induces the inflammatory process by increasing phosphorylation of P38 mitogen activated protein kinases (MAPK).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that TLR-4 was upregulated in microglia after oxygen-glucose deprivation (OGD), that microglia with intact TLR-4 expressed a significantly higher amount of inflammatory cytokines, and that the absence of a functional TLR-4 is associated with a decreased production of inflammatory cytokines. 9,10 In stroke models, TLR-4 has been associated with larger infarct volumes and more severe functional deficits. 11 In addition, ischemic spinal cord also demonstrated a significant increase in microglia with intact TLR-4, suggesting that TLR-4 signaling has an effect on reperfusion injury in the spinal cord.…”
Section: Safflower Yellow Regulates Microglial Polarization and Inhibmentioning
confidence: 99%